Citizens against crime and violence: societal responses in Mexico - Stack, Trevor (Rutgers University Press, 2022)
Introduction: the comparative ethnography of societal responses to crime and violence in Mexico / by Trevor Stack -- Local citizen security councils: sustainable responses to a crisis of trust in state security provision / by Irene Álvarez, Denisse Román, and Trevor Stack -- Cultural activism: mobilizing art and culture to build transformative socio-political fields / by Edgar Guerra and Ariadna Sánchez -- Socio-legal activism in contexts of criminal and institutional violence: challenging forced disappearances, gender violence, and assaults on LGBT and sex workers / by Salvador Maldonado Aranda and Iran Guerrero Andrade -- Churches as institutions in regions of violent organized crime / by Trevor Stack -- A room of their own: barriers to women's activism against the continuum of violence in Michoacán, Mexico / by Catherine Whittaker -- Key objectives, strategic choices and impact of societal responses to violence: lessons for policy and practice / by Pilar Domingo and Sasha Jesperson -- Society to the rescue? Rethinking responses to crime-related violence and corruption / by Trevor Stack.